SURVEI KUALITAS PELAYANAN PEMILU SERENTAK 2019 SEBAGAI BAHAN EVALUASI BERBASIS RISET BAGI KPPU (TPS 42 dan 43 Kelurahan Bandulan Kota Malang) - Catharina Aprilia Hellyani; Seno Aji Wahyono; Novenda Kartika Putrianto (Referensi : Jurnal Ilmu Manajemen dan Akuntansi, 2021)
This study aims to measure 5 levels of service quality to find out how good the service was in the 2019 Simultaneous Election. Service quality was measured by the TERRA dimensions, namely tangibility, empathy, responsiveness, reliability, and assurance with a Likert measurement scale. The object of this research was 280 residents who were active voters at TPS 42 and 43, with a sample of 60 people. The data that has been obtained was processed into descriptive statistical data which were used as a database to determine the dimensions of TERRA which are still not optimal in the next general election. Descriptive data processing showed that most of the respondents strongly agree with the statement of service quality related to the TERRA dimension. The measurement result showedthat the service quality of TPS 42 and 43 is in the high range scale. This shows that the quality of service at TPS 42 and 43 was very good and complies with KPPS guidelines so that it should be used as a role model for other TPS.